Knowledge and associated factors of patients toward informed consent in obstetric and gynecologic surgical procedures at Debre Markos Comprehensive Specialized Hospital, Ethiopia - Ferede, Addisu Andualem; Fetene, Mamaru Getie; Mehiretie, Endinew Beka; Getahun, Worku Taye; Abneh, Aysheshim Asnake (Frontiers in Surgery, 2025)
BackgroundInformed consent (IC) is a principle in medical ethics and medical law that a patient must have adequate information and understanding before making decisions about their medical care. It is very essential for both clinician and patient in surgery and should be seen as a usual activity. Knowledge is one of the main intervention tools to improve patient comprehension in informed consent for surgical patients. In Ethiopia, little is known about the knowledge level and its determinant factors toward obstetric and gynecologic surgical informed consent. Due to this reason, this study aimed to assess the level of knowledge and associated factors of surgical informed consent among patients who underwent obstetric and gynecologic surgery at Debre Markos Comprehensive Specialized Hospital.MethodsAn institutional-based cross-sectional study was conducted from 28 November to 30 December 2023, among 298 postoperative women admitted to Debre Markos Comprehensive Specialized Hospital. Data were collected using a pretested, structured interviewer-administered questionnaire by using a systematic random sampling technique. The collected data were entered into EpiData version 4.6 and then exported to SPSS statistical software version 25 for analysis. A multivariable logistic regression analysis was employed to estimate the effect of independent variables on the outcome variable. An adjusted odds ratio [adjusted odds ratio (AOR)] with a 95% confidence interval (CI) was computed to report the presence of association between the dependent and independent variables. Statistical significance was determined at a P-value of <0.05.ResultsA total of 298 women participated in the study. In this study, the overall good knowledge of women regarding obstetrical and gynecologic surgical informed consent was 42.3% (95% CI: 36.7, 47.9). Urban residence (AOR = 2.32, 95% CI: 1.08, 5.03), educational status of women (AOR = 4.85, 95% CI: 1.99, 11.78), elective type of surgery AOR = 1.8, 95% CI: 1.14, 4.07), and having previous history of surgery (AOR = 7.2, 95% CI: 4.02, 15.15) were the identified determinant factors affecting knowledge of women toward obstetric and gynecologic surgical informed consent.ConclusionIn this study, more than half of the study participants lack overall good knowledge regarding obstetrical and gynecologic surgical informed consent. Residence, educational status, schedule of surgery, and previous history of surgery were the identified determinant factors affecting the knowledge of women toward obstetric and gynecologic surgical informed consent.